Management of field peas to reduce Ascochyta blight and maximise yield - Bennett, Sarita; Lee, Robert C; Sharma, Anjana (2019)
The legume field pea can be a valuable component of crop rotations to reduce cereal disease carryover and increase soil nitrogen. However, it is frequently affected by Ascochyta blight which reduces yield. Fungicides are used to control the impact of the disease with mixed success, but effective management relies on a combination of strategies. To determine the efficacy of management strategies for disease suppression, field trials were run investigating;  The interaction between time-of-sowing and fungicide treatment at three locations in Western Australia in 2016, with four fungicide treatments applied either once or twice after sowing.  The impact of using wheat stubble from the preceding crop to trellis the field peas, reducing crop lodging, and potentially disease spread. Results showed that time of sowing had a greater impact on yield than repeated application of fungicide. Stubble-trellising using the previous year’s cereal stubble significantly reduced disease in the crop and increased yield.